Bridge to terabithia eaudiobook - Paterson, Katherine (Recorded Books Inc., 2015)
All summer, Jess pushes himself to be the fastest boy in the fifth grade, running mile after hilly mile on the family farm. When the year's first schoolyard race is run, his victory is stolen by a new girl who doesn't even know enough to stay off the boys' side of the playground. But instead of becoming rivals, they become friends. Jess guides Leslie, the city girl, through life in the country, and she draws him into the imaginary world of Terabithia. Here, Leslie and Jess are safe from bullies and ridicule. One day, however, that tranquility is shattered when tragedy forces one of them to reign in Terabithia alone. In this poignant, Newbery Medal-winning novel, Katherine Paterson beautifully illustrates the joy and pain of growing up. Narrator Tom Stechschulte's warm, lightly accented voice brings Jess, Leslie and the magical world of Terabithia to life for the listener.